Restrictive influence of SAMHD1 on hepatitis B virus life cycle - Sommer, Andreas; Qu, Bingqian; Ni, Yi; Urban, Stephan (Scientific reports, 2016)
Deoxynucleotide triphosphates (dNTPs) are essential for efficient hepatitis B virus (HBV) replication. Here, we investigated the influence of the restriction factor SAMHD1, a dNTP hydrolase (dNTPase) and RNase, on HBV replication. We demonstrated that silencing of SAMHD1 in hepatic cells increased HBV replication, while overexpression had the opposite effect. SAMHD1 significantly affected the levels of extracellular viral DNA as well as intracellular reverse transcription products, without affecting HBV RNAs or cccDNA. SAMHD1 mutations that interfere with the dNTPase activity (D137N) or in the catalytic center of the histidine-aspartate (HD) domain (D311A), and a phospho-mimetic mutation (T592E), abrogated the inhibitory activity. In contrast, a mutation diminishing the potential RNase but not dNTPase activity (Q548A) and a mutation disabling phosphorylation (T592A) did not affect antiviral activity. Moreover, HBV restriction by SAMHD1 was rescued by addition of deoxynucleosides. Although HBV infection did not directly affect protein level or phosphorylation of SAMHD1, the virus upregulated intracellular dATPs. Interestingly, SAMHD1 was dephosphorylated, thus in a potentially antiviral-active state, in primary human hepatocytes. Furthermore, SAMHD1 was upregulated by type I and II interferons in hepatic cells. These results suggest that SAMHD1 is a relevant restriction factor for HBV and restricts reverse transcription through its dNTPase activity.